A counterexample to a nonlinear version of the Kreĭn–Rutman theorem by R. Mahadevan. (June 2018) - Arapostathis, Ari
Abstract: In this short note we present a simple counterexample to a nonlinear version of the Kreĭn–Rutman theorem reported in Mahadevan (2007). Correct versions of this theorem, and related results for superadditive maps are also presented.